Steganographic method for protection the objects of intellectual properties and intellectual rights - Сагун, Андрей Викторович; Щербак, Леонид Николаевич; Хайдуров, Владислав Владимирович; Кунченко-Харченко, Валентина Ивановна; Костянец, Станислав Олегович; Тетьора, Михаил Сергеевич (Ukrainian Information Security Research Journal, 2017)
The protection of information, marked as intellectual property or copyrights, is a very special technical task, because often it is difficult to define, if this information is legally protected or the protection of information is not of-fered as an option. This task can be partly solved by using the “Copyright Demonstration” script, or by script named as “No Copy” script. In the most cases this method of pro-tection is known as information hiding. As a result, the modification of cryptographic embedded type of LSB–algorithm with keys was developed. The strength of algo-rithm has been improved in comparison with classical ste-gano – LSB–algorithms. The main point of proposed ste-ganographic method is the embedding of full-colored im-ages into dynamic full-colored information objects. This way, if the image pixel intensity level changes from 0 to 255, it means that this image can be represented in eight bit-planes. Accordingly, this method is based on LSB–methodology of information hiding. The article deals with the methodology of system development for protecting and transferring graphic, text data to dynamic graphic objects.The modeling was made in the MATLAB application environment and thus the time depending results were ob-tained. On the basis of the developed LSB–method modi-fication one can improve the protection of intellectual property rights in animated and video graphic objects by embedding the various full-colored digital watermarks. Also, the proposed method may have also a versatile usage.